Sifat Amanah Karyawan Masjid Cheng Hoo Surabaya - Lestari Dwi Astuti; Sri Herianingrum (Universitas Airlangga, 2019)
The Mosque is a place of worship for Muslims. Employees are needed for managing and maintaining Mosques. Working in a Mosque must have a amanah so that employees can be trusted in the continuity of the tasks that have been done. The aims of this study was to find out how the implementation of the amanah of the employees on Cheng Hoo Surabaya Mosque. This study uses descriptive eksplanatoris methods. This study uses interviews and primary data collection. For informants the amanah can show prosperity to itself. Needs will be fulfilled if working with sincerity and amanah. For informants, Economic Indicators that are accepted by Cheng Hoo Mosque employees are sufficient because for the employees of the Cheng Hoo Mosque, the first one is seeking Allah's blessing, not only worldly.Keywords: Implementation, Amanah, Mosque, EmployeesREFFERENCESAbiyoga, Firdaus Arfianandy. 2014.“Implementasi sifat amanah pengelola Koperasi Pondok Pesantren Qomaruddin Desa Sampurnan Kecamatan Bungah Kabupaten Gresik”. Skripsi tidak diterbitkan. Universitas Airlangga.Afifuddin dan Beni Ahmad Saebani. 2009. Metodelogi Penelitian Kualitatif.Bandung: Pustaka Setia.Basir, Bartos. 1990. Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara.Bungin, Burhan. 2008. Penelitian Kualitatif. Jakarta: KencanaDepartemen Pendidikan dan Kebudayaan. 1996. Kamus Besar Bahasa Indonesia.Jakarta: Balai PustakaDuhriah. 2015. Tingkatan-Tingkatan Maqashid Al-Syariah: al-Dharruruyyat, alHajiyyat, dan al-Tahsiniyyat. Jurnal Vol. 01 No. 1 Januari-Juni 2015 hal 191-210.Enggardini, Rohma Vihana. 2016. “Kesejahteraan Karyawan Perspektif Maqashid Syariah pada Pusat Penelitian Kopi dan Kakao Indonesia”. Skripsi tidak diterbitkan. Universitas Airlangga.Fauzia, Abdul Kadir. 2014. Prinsip Dasar Ekonomi Islam. Jakarta : PrenadamediaGroup.Ghani, Muhammad Ilyas Abdul. 2005. Sejarah Masjid Nabawi. Indonesia:Depag.Handoko, T. Hani, 2000. Manajemen Sumber Daya Manusia. Yogyakarta: BPFEHasibuan, Malayu S.P. 2005. Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara.Herianingrum, Sri. 2015. Implementasi Nilai-nilai Amanah pada karyawan Hotel Darussalam Pondok Pesaantren Gontor di Ponorogo. Jurnal. Vol.1 (1)Husna, Amalia. 2009. Amanah (Terpercaya), Cetakan Pertama. Jakarta Timur: IntiMedina.Kusumawardhani, siska hapsari. 2011. Masjid Besar Kecamatan Depok Sleman DiYogyakarta. Skripsi. FT, Pend. Arsitek, Universitas Atma Jaya Yogyakarta.Kurniawan, yamsul. 2014. Masjid dalam Lintas Sejarah Umat Islam. Journal ofIslamic Studies. Vol.4 (2).Merchant, Van der Stede. 2014. Sistem Pengendalian Manajemen: PengukuranKinerja, Evaluasi dan Insentif. Jakarta: Salemba Empat.Moleong, Lexy J. 2000. Metode Penelitian Kualitatif. Bandung: PT. Remaja RosdakaryaNawawi, Syaifuddin. 2008. Memberdayakan Masjid Sebagai Pusat PembinaanEkonomi Umat. Makalah Tidak Dipublikasikan. Suraba: DMI Jatim.Nazir, Mohammad. 2003. Metode Penelitian. Jakarta: Ghalia Indonesia.Paksi, Diera G. 2011. Implementasi Amanah dalam Pemasaran Internal danDampaknya bagi Niat Wali Murid untuk Melanjutkan Studi Anaknya di Sekolah Dasar Islam Al-Azhar Surabaya. Penelitian Tidak Dipublikasikan.Surabaya: Fakultas Ekonomi Universitas Airlangga.Piti. 2001. Laksamana Haji Muhammad Cheng Hoo Bahariwan Kebanggaan Umat Islam.Press Release Siagang, Sondang. 2004. Manajemen Abad 21. Jakarta: Bumi Aksara.Simamora, Henry. 2005. Membuat Karyawan Lebih Produktif dalam Jangka Panjang (Manajemen SDM). Yogyakarta: STIE YKPN.Setiawan, Guntur. 2004. Impelemtasi dalam Birokrasi Pembangunan Balai.Jakarta: Pustaka.Sugiyono. 2010. Metode Penelitian Kuantitatif Kualitatif dan R&D.Bandung:AlfabetaSumandi, Suryabrata. 1994. Metodologi Penelitian. Jakarta: RajawaliSumarsono, Sonny. 2003. Ekonomi Manajemen Sumberdaya Manusia danKetenagakerjaan. Yogyakarta: Graha Ilmu.Usman, Nurdin. 2002. Konteks Implementasi Berbasis Kurikulum. Jakarta:Grasindo.Veithzal, Rivai. 2004. Manajemen Sumber Daya Manusia untuk Perusahaan.Jakarta: Raja Grafindo Persada.Wulandari, Nanada Rizki. 2013. “Implementasi Nilai-Nilai Amanah Tim Pengajae Divisi Kajian dan Diklat Masjid Al-Akbar Surabaya”. Skripsi tidak diterbitkan. Universitas Airlangga.Yani, Ahmad.2007. Panduan Mengelola Masjid. Jakarta: Pustaka LebahZarkhoviche, Baha. 2017. Jejak-Jejak Emas Laksamana Cheng Hoo.Yogyakarta:Araska